Adiposity associated DNA methylation signatures in adolescents are related to leptin and perinatal factors. Issue 8 (3rd August 2022) - Huang, R.C.; Melton, P.E.; Burton, M.A.; Beilin, L.J.; Clarke-Harris, R; Cook, E; Godfrey, K.M.; Burdge, G.C.; Mori, T.A.; Anderson, D; Rauschert, S.; Craig, J. M.; et al.
ABSTRACT: Epigenetics links perinatal influences with later obesity. We identifed differentially methylated CpG (dmCpG) loci measured at 17 years associated with concurrent adiposity measures and examined whether these were associated with hsCRP, adipokines, and early life environmental factors. Genome-wide DNA methylation from 1192 Raine Study participants at 17 years, identified 29 dmCpGs (Bonferroni corrected p < 1.06E-07) associated with body mass index (BMI), 10 with waist circumference (WC) and 9 with subcutaneous fat thickness. DmCpGs within Ras Association (RalGDS/AF-6), Pleckstrin Homology Domains 1 ( RAPH1 ), Musashi RNA-Binding Protein 2 ( MSI2 ), and solute carrier family 25 member 10 ( SLC25A10 ) are associated with both BMI and WC. Validation by pyrosequencing confirmed these associations and showed that MSI2, SLC25A10, and RAPH1 methylation was positively associated with serum leptin. These were  also associated with the early environment; MSI2 methylation (β = 0.81, p = 0.0004) was associated with pregnancy maternal smoking, SLC25A10 (CpG2 β = 0.12, p = 0.002) with pre- and early pregnancy BMI, and RAPH1 (β = −1.49, p = 0.036) with gestational weight gain. Adjusting for perinatal factors, methylation of the dmCpGs within MSI2, RAPH1, and SLC25A10 independently predicted BMI, accounting for 24% of variance. MSI2 methylation was additionally associated with BMI over time (17 years old β = 0.026, p = 0.0025; 20 years old β = 0.027, p = 0.0029) and between generations (mother β = 0.044, p = 7.5e-04). Overall findings suggest that DNA methylation in MSI2, RAPH1, and SLC25A10 in blood may be robust markers, mediating through early life factors.